A Survey paper on Rural Smart Village using Internet of Things - Seth, Rakhi (International Journal of Computer Sciences and Engineering, 2025)
This paper is about the IOT usage in developing smart rural villages which need the prime focus in terms of development, growth, and progress. Rural villages have too many scope of development which provides a way to implement different innovative ideas which change the face of rural India. Different technique provides the idea about different innovation in the field of IOT. In this paper we also tell about what is IOT and how it is implemented in development of smart village.